Vitamin D Deficiency Prevalence And Its Association with Bacterial Load Sputum in Newly Diagnosed TB Patients - Melviana Lubis; Bintang Yinke Magdalena Sinaga; Nita Andriani Lubis (Faculty of Medicine, Universitas Padjadjaran, 2020)
Vitamin D plays a role in innate and adaptive immune functions, and its deficiency has become a risk factor for TB infection. This study aimed to describe the prevalence of vitamin D deficiency in newly diagnosed TB patients and to examine the relationship between vitamin D levels and sputum smear positivity that reflects bacterial load. This is a cross-sectional study conducted at several primary health care facilities in Medan and Deli Serdang from November 2015 to June 2016. As many as 86 subjects adult TB patients with positive smear sputum who had not received therapy or had at most 1 week on therapy were recruited. Sputum examination were interpreted using IUATLD (International Union Against Tuberculosis and Lung Disease) grading scale. Serum 25 (OH) vitamin D level was estimated using enzyme-linked immunosorbent assay (ELISA) and interpreted as deficiency (<20 ng/ml), insufficiency (20–29 ng/ml), or optimum (30–100 ng/ml). The association between vitamin D level and positivity level of AFB sputum was analyzed using Spearman correlation test. The prevalence of VDD in new pulmonary TB patients with positive smear sputum was 17.4%. There was a weak relationship between vitamin D level and positivity level of AFB sputum (p = 0.014), with a correlation coefficient of (-0.264). Many of newly diagnosed TB patients had vitamin D deficiency despite the fact that Indonesia is an equatorial area with sufficient sunshine throughout the year. This study shows vitamin D indeed affect bacterial load and a low 25 (OH) vitamin D level is associated with higher bacterial load. Prevalensi Defisiensi Vitamin D pada Pasien TB Paru Baru dan Hubungan dengan Derajat Kepositifan Sputum Basil Tahan AsamVitamin D berperan dalam imunitas bawaan dan adaptif. Kekurangan vitamin D merupakan faktor risiko terinfeksi TB. Penelitian ini bertujuan menggambarkan prevalensi defisiensi vitamin D pada pasien TB baru dan mengetahui hubungan kadar vitamin D dengan derajat kepositifan sputum yang mencerminkan kepadatan bakteri. Penelitian potong lintang ini dilakukan di beberapa Puskesmas di wilayah Medan dan Deli Serdang pada November 2015 hingga Juni 2016. Subjek penelitian sebanyak 86 pasien TB dewasa dengan sputum basil tahan asam (BTA) positif, yang belum atau maksimal 1 minggu mengkonsumsi obat. Pemeriksaan sputum dinilai menggunakan skala IUATLD. Kadar vitamin D serum 25 (OH) dinilai dengan metode ELISA dan diklasifikasikan menjadi defisiensi (<20 ng/mL), insuffisiensi (20–29 ng/mL), optimum (30–100 ng/mL). Hubungan kadar vitamin D dengan tingkat kepositifan sputum BTA dilakukan dengan uji korelasi Spearman. Prevalensi VDD pada pasien TB paru baru dengan sputum positif adalah 17,4%. Terdapat hubungan antara kadar vitamin D dan tingkat kepositifan sputum BTA (p=0,014), dengan koefisien korelasi (-0,264). Banyak pasien TB paru baru yang mengalami kekurangan vitamin D, meskipun Indonesia berada di khatulistiwa dengan kecukupan sinar matahari sepanjang tahun. Penelitian ini menunjukkan bahwa vitamin D berhubungan dengan kepositifan sputum dan kadar vitamin D yang rendah berhubungan dengan kepadatan bakteri yang lebih tinggi.